Effect of temperature change on refractive index of an egg white and yolk: a preliminary study - Sokołowski, Patryk (Photonics Letters of Poland, 2022)
In this article, the refractive index of an egg white and yolk depending on temperature in range 30 - 47 °C over 1550 nm was determined. The measurement head was constructed as fiber optic Fabry-Perot interferometer with interference between polished fiber end-face and aluminum weighing dish. The measurement setup has been made of an optical spectrum analyzer, a superluminescent diode with a central wevelength of 1550 nm, 2:1 fiber coupler and heat plate. Full Text: PDF References P. Magdelaine, "Egg and egg product production and consumption in Europe and the rest of the world, Improving the Safety and Quality of Eggs and Egg Products", Egg Chemistry, Production and Consumption, 3 (2011). CrossRef H. Kuang, F. Yang, Y. Zhang, T. Wang, and G. Chen, "The Impact of Egg Nutrient Composition and Its Consumption on Cholesterol Homeostasis", Cholesterol (2018). CrossRef J. Gienger, K. Smuda, R. Müller, M. Bär, and J. Neukammer, "Refractive index of human red blood cells between 290 nm and 1100 nm determined by optical extinction measurements", Sci. Rep. 9, 1 (2019). CrossRef P. Listewnik, M. Hirsch, P. Struk, M. Weber, M. Bechelany, and M. Jędrzejewska-Szczerska, "Preparation and Characterization of Microsphere ZnO ALD Coating Dedicated for the Fiber-Optic Refractive Index Sensor", Nanomaterials 9, 2 (2019) CrossRef Y. Wu, Y. Zhang, J. Wu, and P. Yuan, "Fiber-Optic Hybrid Structured Fabry-Perot Interferometer Based On Large Lateral Offset Splicing for Simultaneous Measurement of Strain and Temperature", J. Lightwave Technol., 35, 19 (2017). CrossRef M. Islam, M. Mahmood, M Lai, K. Lim, and H. Ahmad, "Chronology of Fabry-Perot Interferometer Fiber-Optic Sensors and Their Applications: A Review", Sensors 14, 4 (2014). CrossRef K. Karpienko, M. Wróbel, and M. Jędrzejewska-Szczerska, "Determination of refractive index dispersion using fiber-optic low coherence Fabry-Perot interferometer: implementation and validation", Opt. Eng. 53, 7 (2014). CrossRef M. Kosowska, D. Majchrowicz, K. Sankaran, M. Ficek, K. Haenen, and M. Szczerska, "Doped Nanocrystalline Diamond Films as Reflective Layers for Fiber-Optic Sensors of Refractive Index of Liquids", Materials 12, 13 (2019). CrossRef G. Xiao, A. Adnet, Z. Zhang, F. Sun, and C. Grover, "Monitoring changes in the refractive index of gases by means of a fiber optic Fabry-Perot interferometer sensor", Sensors and Actuators 118, 2 (2005). CrossRef